Students Learning to Use the Skills Used by Practicing Scientists - Akcay, Hakan; Yager, Robert E. (EURASIA, 2016)
The purpose of the study was to examine the effectiveness of a Science Technology and Society (STS) approach in terms of student understanding of major processes of science. Participants included twelve teachers who agreed to participate in an experimental study where Science, Technology, and Society (STS) strategies were utilized with one class section and in a school class where the teacher determined the course structure and the form of instruction (textbook-oriented) that is typically used by most science teachers. A total of twenty-four sections of students were in STS sections (199 students) and a similar number in textbook-oriented sections (204 students). The data collected were analyzed using quantitative methods. The results indicate that students in the STS sections achieved significantly better than students in the textbook-oriented sections in terms of understanding and using science process skills. Differences in success by male and female students of varying ability levels were examined as well.
Keywords: science process skills; science technology and society (sts); science teaching and learning; professional development; TEACHERS; Education & Educational Research